How to read the Bible for all its worth - Fee, Gordon D; Stuart, Douglas K (Grand Rapids, Mich. : Zondervan, 2003)
Understanding the Bible isn't for the few, the gifted, the scholarly. The Bible is accessible. It's meant to be read and comprehended by everyone from armchair readers to seminary students. A few essential insights into the Bible can clear up a lot of misconceptions and help you grasp the meaning of Scripture and its application to your 21st-century life. More than half a million people have turned to How to Read the Bible for All Its Worth to inform their reading of the Bible. This third edition features substantial revisions that keep pace with current scholarship, resources, and culture. Changes include: *Updated language *A new authors' preface *Several chapters rewritten for better readability *Updated list of recommended commentaries and resources Covering everything from translational concerns to different genres of biblical writing, How to Read the Bible for All Its Worth is used all around the world. In clear, simple language, it helps you accurately understand the different parts of the Bible-their meaning for ancient audiences and their implications for you today-so you can uncover the inexhaustible worth that is in God's Word. --
Bible
Introduction : the need to interpret -- The basic tool : a good translation -- The Epistles : learning to think contextually -- The Epistles : the hermeneutical questions -- The Old Testament narratives : their proper use --
Includes bibliographical references and indexes
Keywords: Bible -- Study and teaching